PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. Suara Merdeka Press Semarang) - Vega Isma Adhika; Rodhiyah Rodhiyah; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2014)
Human resources is one of factors has an important role in improving employee performance. The population of this study were 93employees as respondent. From the results of data analysis conclude that Culture Organization has significant effect on Employe Performance of 56.3 percent. Commitment affect empoye performance by 67 percent. . Culture Organization and Commitment simultaneously affecting Employe Performance by 69.2 percent. . Based on these results, the management of PT. Suara Merdeka Press Semarang needs to consider the application of Culture Organization by division supervisor. Continuous guidance and supervision needs to be done so that employees work better. e needs of employees and the opportunity to move forward should be supported and facilitated.